Synthesis and in vitro antibacterial activity of new aminothiazole-oximepiperidone cephalosporins. (15th May 2021) - Shen, Zhengwu; Xu, Wei; Yu, Jingfeng; Chen, Lixia; Zhang, Jinghua; Sheng, Sihan; Dong, Xun; Bian, Hongzhu
Graphical abstract: Abstract: Four new aminothiazole-oximepiperidone cephalosporins (10a-10d ) were synthesized, with their in vitro antibacterial activities against hospital isolated Gram-negative bacteria assessed. The results showed that compounds 10a-10d effectively inhibit a variety of Gram-negative bacteria. Compound 10a was the most potent compound, with comparable activity as ceftazidime. The combination of compound 10a and Avibactam was very active against almost all bacteria tested, which including multidrug resistant K. pneumoniae and A. baumannii. Compared to Avycaz, this combination is more potent against ESBL producing K. pneumoniae . Thus, the combination of 10a and Avibactam is of interest for further studies.